Experimental and numerical analysis of the heat generated by plastic deformation in quasi-static uniaxial tensile tests. (July 2020) - Neto, D.M.; Simões, V.M.; Oliveira, M.C.; Alves, J.L.; Laurent, H.; Oudriss, A.; Menezes, L.F.
Highlights: Experimental and numerical analysis of the temperature rise in the quasi-static uniaxial tensile tests. The predicted temperature rise is almost independent of the selected heat transfer coefficients. Comparison between the Zehnder model and the Aravas model. Taylor–Quinney coefficient increases as the plastic deformation accumulates for the aluminium alloy AA6016-T4. Abstract: This study evaluates the temperature variation observed in quasi-static uniaxial tensile tests, due to the heat generated by plastic deformation. The AA6016-T4 aluminium alloy was the material selected, considering different values of crosshead velocity (from 0.01 mm/s up to 1 mm/s). The temperature variation was also evaluated during the stress relaxation test. A finite element model of the uniaxial tensile test is presented, which takes into account the heat generated by plastic deformation, as well as the effect of the heat losses to the environment (convective heat transfer coefficient) and to the grips (interfacial heat transfer coefficient). The numerical results show that the predicted temperature variation is almost independent of the selected heat transfer coefficients. On the other hand, the temperature rise is influenced by the Taylor–Quinney coefficient. The comparison between experimental and numerical temperatures shows that the Zehnder model (increasing Taylor–Quinney coefficient) provides more accurate results than the Aravas model (decreasing Taylor–Quinney coefficient). Nevertheless, the evolution of the Taylor–Quinney coefficient defined by the Zehnder model assumes a constant value for the hardening coefficient, which does not fit the hardening behaviour observed for this aluminium alloy.